Corporate Social Responsibility under the Maqasid Syariah Concept in Malaysia: Why Does it Matter? - Abd Aziz, Hartinie; Abd Ghadas, Zuhairah Ariff; Ossofo, Assane Buana (Jurnal Media Hukum, 2023)
Corporate Social Responsibility (CSR) is an essential component of the shariah corporation framework. In the current corporate model, CSR is still an option rather than a company objective. The need for CSR is still being debated among companies, with some believing that it is in the long-term self-interest of a business to be socially responsible, while others view CSR as weakening a business's primary purpose. Islamic law requires Muslims to not only be governed by the al-Quran and as-Sunnah but also to be subject to the objective of Syariah, namely Maqasid Syariah. The research aims to provide analysis and recommendations to improve the practice of CSR according to the concept of Maqasid Syariah. This qualitative research used doctrinal  legal method with employing secondary data. The outcome of this research is significant as a basis for law reform to develop a Shariah Compliant Corporation. It is crucial to incorporate CSR into the Shariah-compliant business model to ensure that businesses are responsible not only for maximizing profits but also for contributing positively to society. The incorporation of CSR into the Syariah-compliant business model is crucial in achieving the objectives of Syariah, namely, the promotion of human welfare, justice, and sustainability